INTEGRATING LARAVEL 8 AND NODE.JS FOR DEVELOPING WHATSAPP COMMUNICATION MEDIA FOR NEW STUDENT ENROLLMENT IN THE FACULTY OF SCIENCE AND TECHNOLOGY - Harminto Mulyo; Nadia Annisa Maori (Science and Technology (SciTech), 2024)
The promotional process is a crucial initial stage for higher education institutions. New student admissions are a critical aspect that serves as a benchmark for enhancing the institution's appeal and reputation. To improve efficiency and effectiveness, this study proposes a WhatsApp-based communication system integrated with Laravel 8 and Node.js, ensuring faster, consistent, and easily accessible responses. Using the Define-Design-Develop-Disseminate (4D) Model, this study integrates Laravel 8 and Node.js to develop a WhatsApp communication system for new student admissions. This approach includes identifying needs, designing the system, developing a prototype, conducting large-scale testing, and dissemination. The proposed system architecture consists of two main components: a backend developed with Laravel 8 and a WhatsApp communication module managed using Node.js and Baileys. Laravel 8 handles the WhatsApp bot, including keyword processing, message sending, and contact management. Meanwhile, Node.js with Baileys directly interacts with the WhatsApp API, facilitating real-time message delivery and reception. The integration of Laravel 8 and Node.js in the WhatsApp communication application at the Faculty of Science and Technology, UNISNU Jepara, has proven to be efficient and responsive. This system enhances message management, bot functionality, and contact handling, significantly improving response speed and efficiency in addressing prospective student inquiries.